2016
DOI: 10.5603/gp.2016.0030
|View full text |Cite
|
Sign up to set email alerts
|

The role of early determination of β-human chorionic gonadotropin levels in predicting the success of single-dose methotrexate treatment in ectopic pregnancy

Abstract: Objective: The aim of the study was to determine the importance of β-hCG level on day 4 following methotrexate (MTX) administration, and the difference between β-hCG levels assessed on day 0 and day 4 in predicting treatment success. Material and methods:A total of 68 women with tubal pregnancy, treated with a single dose of MTX, were selected for this retrospective study. Results:The success rate of single-dose MTX treatment in our clinic was 75% (51/68). Among 51 patients in whom MTX treatment was successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Çelik et al reported that a decreased percentage between days 1 and 4 did not seem to be a better predictor than that between days 4 and 7. 31 Girija et al reported that the MTX treatment could be successful not only in patients whose serum β-hCG levels decreased on the 4 th day, but also those whose serum β-hCG level increased on the 4 th day. They observed that a >50% increase in serum β-hCG levels in the first 4 days significantly increased the risk of MTX treatment failure, as in our study.…”
Section: Variablementioning
confidence: 99%
“…Çelik et al reported that a decreased percentage between days 1 and 4 did not seem to be a better predictor than that between days 4 and 7. 31 Girija et al reported that the MTX treatment could be successful not only in patients whose serum β-hCG levels decreased on the 4 th day, but also those whose serum β-hCG level increased on the 4 th day. They observed that a >50% increase in serum β-hCG levels in the first 4 days significantly increased the risk of MTX treatment failure, as in our study.…”
Section: Variablementioning
confidence: 99%
“…Side effects such as bone marrow depression, hepatotoxic, nephrotoxic mouth and intestinal mucosa are side effects. In addition, the effects of the drug are antagonized by externally administered folinic acid [13].…”
Section: Introductionmentioning
confidence: 99%